A system dynamics approach to measure the effect of information sharing on manufacturing/remanufacturing systems' performance. Issue 8 (3rd August 2022) - Delavar, Hamed; Gilani, Hani; Sahebi, Hadi
ABSTRACT: Nowadays, the necessity to measure, control, and improve manufacturing systems' economic and environmental performances is becoming vital to achieve competitive advantages. To deal with these challenges, closed-loop supply chain networks are a very useful concept to reduce the manufacturing systems' total cost and environmental impacts. Hence, in this work, particular focus is given to the closed-loop supply chain management to reduce, reuse, remanufacture, and recycle the used products. In this regard, in this study, the authors propose a closed-loop supply chain model, including a manufacturer and a retailer. Decision and policymaking in such a real supply network is very complex. As a result, a system dynamics model has been developed to provide a computer-integrated network, measure, control, and improve the impact of parameters' variation, such as information sharing, on the electronics product manufacturing system's performance bullwhip effect sensitivity analysis. The results show that the appropriate policy and electronic recovery effectively can reduce the bullwhip effects, increase economic performance, and reduce the proposed closed-loop supply chain components' order preparation time and return rate. Finally, the paper uses an LED panel manufacturer's case to validate the application of the methodology and verify the results.